Setting the table: cultivating Fort Collins community health through accessible food security solutions - Vande Plasse, Addison, author (Colorado State University. Libraries, 2024)
Food security is a cornerstone of public health, yet many individuals in Fort Collins face significant barriers to accessing nutritious food. My Honors Thesis, Setting the Table: Cultivating Fort Collins Community Health Through Accessible Food Security Solutions, addresses these challenges by enhancing the visibility and accessibility of local food pantries. This project involved creating a user-friendly website and distributing posters with QR codes to connect underserved populations to essential resources. Through these efforts, I aimed to reduce stigma, improve awareness, and support chronic health condition management by increasing access to nutritious food. Using data collected from the Fort Collins community and the FMC Food Pantry, this project identified barriers such as lack of awareness, accessibility issues, and the perceived stigma of using food pantries. The website includes comprehensive information on pantry services, tailored to meet diverse needs, such as dietary restrictions and disability accommodations. By October 2024, the project demonstrated measurable impact, with QR code scans averaging 17 per day and increased community engagement. This thesis highlights the critical role of food pantries in public health interventions, bridging the gap between food insecurity and health equity. By addressing food access as a social determinant of health, this work contributes to reducing disparities and fostering a healthier, more resilient community in Fort Collins. The project also inspired initiatives like a dental supply drive, underscoring the interconnectedness of food security and overall wellness. My ultimate goal is to apply these insights in my future career as a public health dentist, integrating health equity principles into comprehensive care for underserved populations.
Colorado State University Honors Program.